Sladkorna bolezen in nosečnost - Kovačec, Simona (Zdravniški vestnik, 2012)
Given the increasing prevalence of obesity, type 2 diabetes mellitus (T2DM), and gestational diabetes mellitus (GDM), the number of women who have some form of diabetes during their pregnancies is increasing. Diabetes in pregnancyentails an increased risk of perinatal mortality and morbidity, as well as complications in mother. These are mainly the result of fetal exposureto maternal hyperglycaemia. Undelayed achievement of normoglycemia is therefore crucial for optimizing maternal and fetal outcomes in all women withdiabetes during pregnancy, regardless of the type of diabetes. In light ofthis, we would like to address the importance of early detection of likely prepregnancy diabetes - mostly T2DM, and the value of preconception care in women with preexisting T2DM and type 1 diabetes mellitus (T1DM). This review is aimed to discus pregestational and gestational diabetes and the associated health risk to the developing fetus and the mother. The management should takeinto account the clinical evidence-based guidelines for the treatment of T2DM published by the Slovenian Endocrine Society in June 2011.
Keywords: human pregnancy; nosečnost; sladkorna bolezen